I love you, good night - Buller, Jon, 1943-; Schade, Susan (New York : Simon and Schuster Books for Young Readers, 1988)
At bedtime, mother and child tell how much they love each other.
2.0
K-3
Keywords: Bedtime -- Fiction; Mother and child -- Fiction; Stories in rhyme; Bedtime -- Fiction; Mother and child -- Fiction; Stories in rhyme